Utilization Of Seaweed (Eucheuma cottoni) And Avocado Seeds (Persea americana) For Making Capsules - Ashar, Husnaini; Ummu Kalsum (Cognitia : International Engineering Journal, 2025)
Capsules are solid preparations consist of the drug in a soluble hard or soft shell. Capsules are generally made by gelatin, it can also be starch or other suitable ingredients. The manufacture of capsules can be derived from seaweed in terms of abundance which can be used as raw material for making natural and halal capsules. Polysaccharide-based seaweed contains sodium, magnesium and calcium which are bound to sulfate ester groups. In addition, avocado seeds also have the potential with 80.1% starch content. The stages in the research are processing seaweed to be carrageenan, making avocado seed flour and making capsules.The carrageenan that produced according the FAO (Food agriculture Organization) standards including moisture, ash, viscosity, gel strength and heavy metals. This study has combined the ratio between avocado seeds and seaweed with a ratio of 1: 1; 1: 2; 1: 3, 2: 1; 2: 2; 2:3; 3: 1, 3: 2; 3: 3. The capsules obtained have a moisture content ranging from 14- 31%. Total Plate Figures (ALT) indicate the number of microbes in a productaccording with SNI 7388: 2009. For the tensile strength have the high tensile strength is ratio avocado seeds and seaweed (2: 3), while the high modulus young is a ratio of 1: 1. Therefore, the raw material for capsules from seaweed and avocado seeds effects the characteristics of the capsules and can be use as natural and halal capsules to replace gelatin.